FLORENSKYITE, FETIP, A NEW PHOSPHIDE FROM THE KAIDUN METEORITE - Ivanov A.V.; Zolensky M.E.; Saito A.; Ohsumi K.; Yang S.V.; Kononkova N.N.; Mikouchi T. (My University, 2000)
Florenskyite is a new phosphide species from the Kaidun chondritic meteorite, which fell in South Yemen in 1980. Kaidun is a unique chondritic breccia containing a huge variety of fragments of different chondritic types. Florenskyite was found as four dispersed grains with a maximum dimension of 14 μm within a single mass of Fe-rich serpentine within one Kaidun clast. Florenskyite is associated with submicrometer-sized grains of pentlandite and small (up to 1.5 μm in width) laths of a still uncharacterized Fe-Cr phosphide. Florenskyite is creamy white in reflected light, and its luster is metallic. The average of three electron microprobe analyses gave (wt%) Fe 40.52, Ti 30.08, Ni 5.47, Cr 0.93, V 0.91, Co 0.60, P 21.69, Si 0.59, sum 100.79, corresponding to Fe1.01(Ti0.87Ni0.13Cr0.03V0.02Co0.01)1.06(P0.97Si0.03). Single-crystal structure analysis was performed on florenskyite using a Laue pattern collected from a multiple crystal by in-situ synchrotron X-ray diffraction. Florenskyite crystallizes in the space group Pnma, and has the anti-PbCl2 structure. Previously determined cell constants of synthetic material [a = 6.007(1), b = 3.602(1), c = 6.897(1) Å] were used in the single-crystal data reduction. We used the POWD12 program to calculate a powder XRD pattern; the 5 most intense reflections are d = 2.301 (I = 100), 2.188 (88), 2.307 (47), 1.938 (45), and 1.801 Å (45). Florenskyite is only the fourth phosphide to be described from nature. Its paragenesis may be unique, and may be due to melting of a mineral assemblage including Fe-Ni metal, schreibersite, daubreelite, osbornite, or heideite and subsequent crystallization of phosphides from the melt.